2010
DOI: 10.1002/pro.437
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and kinetic mechanism of aminoglycoside phosphotransferase‐2″‐IVa

Abstract: Acquired resistance to aminoglycoside antibiotics primarily results from deactivation by three families of aminoglycoside-modifying enzymes. Here, we report the kinetic mechanism and structure of the aminoglycoside phosphotransferase 2 00 -IVa (APH(2 00 )-IVa), an enzyme responsible for resistance to aminoglycoside antibiotics in clinical enterococcal and staphylococcal isolates. The enzyme operates via a Bi-Bi sequential mechanism in which the two substrates (ATP or GTP and an aminoglycoside) bind in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 47 publications
5
39
1
1
Order By: Relevance
“…We and others have shown that APH(2Љ)-IIa and -IVa have comparable relative affinities for both ATP and GTP, whereas the two others preferentially bind GTP, an indication that GTP and not ATP is the physiological cosubstrate for these enzymes (9,10). Contrary to what has been reported for the APH(2Љ)-Ia domain of the bifunctional enzyme, our kinetic characterization of APH(2Љ)-IIa, -IIIa, and -IVa demonstrated that 4,5-disubstituted antibiotics and the atypical aminoglycoside neamine are not substrates, but inhibitors of these enzymes (11)(12)(13). In light of the substantial differences in the reported substrate specificities of APH(2Љ)-Ia and the remaining members of the APH(2Љ) subfamily of aminoglycoside kinases and the discovery that GTP, and not ATP, is the preferred cosubstrate for APH(2Љ)-Ia, we sought to reevaluate the nucleotide and aminoglycoside substrate profiles of the clinically important AAC(6Ј)-Ie/APH(2Љ)-Ia enzyme.…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…We and others have shown that APH(2Љ)-IIa and -IVa have comparable relative affinities for both ATP and GTP, whereas the two others preferentially bind GTP, an indication that GTP and not ATP is the physiological cosubstrate for these enzymes (9,10). Contrary to what has been reported for the APH(2Љ)-Ia domain of the bifunctional enzyme, our kinetic characterization of APH(2Љ)-IIa, -IIIa, and -IVa demonstrated that 4,5-disubstituted antibiotics and the atypical aminoglycoside neamine are not substrates, but inhibitors of these enzymes (11)(12)(13). In light of the substantial differences in the reported substrate specificities of APH(2Љ)-Ia and the remaining members of the APH(2Љ) subfamily of aminoglycoside kinases and the discovery that GTP, and not ATP, is the preferred cosubstrate for APH(2Љ)-Ia, we sought to reevaluate the nucleotide and aminoglycoside substrate profiles of the clinically important AAC(6Ј)-Ie/APH(2Љ)-Ia enzyme.…”
contrasting
confidence: 88%
“…Recent kinetic and x-ray crystallographic studies of three APH(2Љ) phosphotransferases, APH(2Љ)-IIa, -IIIa, and -IVa, revealed that these enzymes possess structural templates for the binding of both ATP and GTP (13,25,26). The availability of both structural templates accounts for the ability of APH(2Љ)-IIa and -IVa to use both ATP and GTP as cosubstrates.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless, the 4,5-disubstituted and atypical aminoglycosides are at most very poor substrates for the APH(2Љ)-If and APH(2Љ)-Ia phosphotransferases, and this finding is consistent with the MIC data, which show no resistance to these antibiotics (Table 1). These data are also in good agreement with the substrate profiles of three other APH(2Љ) enzymes, none of which showed the ability to efficiently phosphorylate 4,5-disubstituted or atypical aminoglycosides (22,24,25). Next, we tested neomycin B, paromomycin, lividomycin A, and neamine as inhibitors, and overall, 4,5-disubstituted aminoglycosides are better inhibitors of APH(2Љ)-If than the APH(2Љ)-Ia domain of the bifunctional enzyme (Table 3).…”
Section: Resultssupporting
confidence: 83%
“…Members of this enzyme family, APH(2Љ)-Ia, -IIa, -IIIa, and -IVa are bisubstrate enzymes that phosphorylate aminoglycoside antibiotics using GTP and/or ATP as the phosphate donor (23). The recently determined X-ray crystal structures of three of these enzymes, APH(2Љ)-IIa, -IIIa, and -IVa, have shed light on substrate recognition and NTP selectivity by these aminoglycoside kinases (24,30,31). In our quest for novel APH(2Љ) phosphotransferases, we analyzed the amino acid sequences of enzymes deposited in the database of the National Center for Biotechnology Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation